BNCC e a língua inglesa: abordagens de ensino em livros didáticos do ensino médio - Freitas, Claudivan Alexandre de (2023)
The Common National Curricular Base (BNCC) brought about challenging adjustments to how English language instruction and learning were handled in the context of schools, of which I specifically point out the acceptance of English as an international lingua franca and the need for activities that take communicative goals in the classroom into consideration. This explicit connection among transformations, challenges and pragmatic approaches emerges during the implementing period of the contested New High School and the latest edition of the National Textbook Plan, the PLND 2021. Following that, this study analyzes five high school textbooks published by different publishers that were picked by the current PNLD, in order to investigate their theoretical-methodological approach. To accomplish this, along with the BNCC, I relied on the theoretical-methodological principles of the communicative approach to English language teaching (Communicative Language Teaching - CLT) through the ideas of Richards (2001, 2016); for foundations in the flow of English studies as a Foreign Language (EFL), the contributions of Nunan (2003), Brown (2007) and Celce-Murcia (2014) Richard and Rodgers (2014), and Oliveira (2014 , 2015) through his contributions to the English teaching context in Brazil. Thus, within the investigative environment offered by the expansive field of Applied Linguistics, the methodological question was established through a qualitative approach, which its actions, here, led to the development and subsequent application of an evaluation board that contains categories of analysis based, mostly on the principles of the BNCC and the CLT guided by the demand of the development of the communicative ability in high school students, which enabled the mapping, description, and analysis of the didactic-pedagogical proposals in these manuals, putting an emphasis on the theoretical-methodological nature, on the themes and their contextualization, on the treatment given to vocabulary and grammatical topics, on the actions that involve the articulation between communicative abilities and competences, and on the role of classroom agents as users of these didactic tools .On the whole, I draw attention to the fact that, despite the identification or recognition of didactically structural fragilities, our educational system is currently making slow but interesting progress toward an understanding of practices that demand and also make possible what is truly important for an approach that effectively supports learners' communicative development.